208k views
3 votes
5(1 + 4m) – 2m = -13

2 Answers

5 votes


\longrightarrow{\green{ \: m = - 1 }}


\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}


5 \: (1 + 4m) - 2m = - 13


\: 5 + 20m - 2m \: = \: - 13


\: 18m = - 13 - 5


\: 18m = - 18


\: m = ( - 18)/(18)


\: m = - 1


\large\mathfrak{{\pmb{\underline{\blue{To\:verify}}{\blue{:}}}}}


5 \: (1 + 4 * - 1) - 2 * - 1 = - 13


\: 5 \: (1 - 4) + 2 = - 13


\: 5 * ( - 3) + 2 = - 13


\: - 15 + 2 = - 13


\: - 13 = - 13


\: L.H.S.=R. H. S

Hence verified.


\bold{ \green{ \star{ \orange{Mystique35}}}}⋆

User Galloglass
by
5.0k points
5 votes

Answer and Step-by-step explanation:

Solve for m.

First, distribute the 5.

5 + 20m - 2m = -13

Combine like terms.

5 + 18m = -13

Subtract 5 from both sides of the equation.

18m = -18

Divide by 18 to both sides of the equation.

m = -1 <- This is the answer.

#teamtrees #PAW (Plant And Water)

User Anilcemsimsek
by
5.8k points